Ergebnisse der Albanien-Expedition 1961 des Deutschen Entomologischen Institutes. 20. Beitrag: Psocoptera. - Giese, Brigitte (Contributions to Entomology = Beiträge zur Entomologie, 1964)
Apart from a survey of the Psocoptera known from the Balkan countries (33 species) there are summarized those species which were found up to now on Albania. The expedition collected only one specimen of Metylophorus nebulosus (Stephens). This species is new to Albania. There are 3 species known from Albania now.